Multiple Myeloma with Suspected Non-Secretory Type - Indrarsi, Annisa Ginar; Sukorini, Usi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Multiple Myeloma (MM) is a hematological malignancy characterized by clonal plasma cell in bone marrow that produceabnormal globulin, which resulted in monoclonal gammopathy. Multiple Myeloma Non-Secretory (MMNS) is a very rareform of multiple myeloma with monoclonal plasmocytic proliferation in bone marrow supported by clinical manifestationand radiological findings. However, plasma cells fail to secrete immunoglobulin. A 44-year-old female came to SardjitoGeneral Hospital with main complaints of weakness and back pain. General weakness and pale palpebral conjunctiva were6 observed (+/+), liver and spleen were not palpable. Blood test results were as follows: Hb 3.0 g/dL, RBC 1.07 x 10 / μL, WBC3 3 562 x 10 /μL, PLT 114 x 10 /μL, A/G ratio 1.07, BUN 51.5 mg/dL, creatinine 4.62 mg/dL, and calcium 3.1 mmol/L. Skeletalsurvey suggested a multiple osteolytic. Protein electrophoresis revealed hypogammaglobulinemia with no M-spike. Therewere 66% of plasma cells in bone marrow. Patient was diagnosed by MMNS. Diagnosis MMNS can be established if clonalplasmacytes is accompanied with renal insufficiency and hypercalcemia. However, monoclonal gammopathy was not foundin serum protein electrophoresis. A case reported of 44-year-old female diagnosed as MMNS with 'punched out' multipleosteolytic, increased plasma cells in bone marrow without evidence of paraprotein in circulation proved by low A/G ratio andnegative M-spike.